Câncer colorretal: aspectos epidemiológicos no estado do Maranhão - ALMEIDA, Joelson dos Santos (2020)
Introduction: Colorectal cancer is a malignant neoplasm that affects the segment of the large intestine (colon, rectum and anus). It usually arises from adenomatous polyps, if left untreated to evolve into malignant tumors in this way, early diagnosis and appropriate treatment can cure the sick by promoting greater chances of survival. Objectives: to analyze the epidemiological aspects of registered cases of colorectal cancer from 2013 to 2017 in the state of Maranhão. Methodology: this is a cross-sectional, retrospective study with a quantitative approach. The research was carried out at the Aldenora Bello hospital using the Health Information System of the Hospital Cancer Registry with data on 421 colorectal cancer cases recorded from 2013 to 2017 in the state of Maranhão. The R software in which the Pearson test was used was used for statistical analysis, considering the significance level of 5% (p <0.05). Results: There were predominant cases in women (55.3%), race / brown color, married, aged 60-70 years (CI: 25.1-33.9), low education and farmers. In clinical aspects, colon cancer was more incident 36.1%, histological type adenocarcinoma, stage IV 27.6% and without metastasis 74.3% of cases. Regarding the examinations performed, clinical examination and clinical pathology, imaging exams, pathological anatomy, 79.1%, received treatment, surgery and chemotherapy 19% of the cases, 26% of the patients had complete remission and 37.5% of the patients took more than 61 days to start treatment. Conclusion: Colorectal cancer is a global public health problem due to the challenge of changing the modifiable risk factors in the population and in the state of Maranhão. It is necessary to implement strategies and expand actions for screening, prevention and timely diagnosis, since the elderly without a history of cancer are at risk, in order to reduce the impacts of the morbidity and mortality of the neoplasia.